P370 INNOVATIVE TELEMONITORED MODEL OF PHYSICAL EXERCISE PRESCRIPTION IN SECONDARY PREVENTION DURING THE QUARANTINE. (18th May 2022) - Lordi, R; Veronese, S; Piccinini, A; Ferro, A; Zerbini, V; Piva, T; Raisi, A; Mandini, S; Grazzi, G; Sassone, B; Pasanisi, G
Abstract: Introduction: COVID–19 pandemic induced the emanation of extraordinary measures like quarantine, that can be considered a risk factor for both physical and mental health in the population. In particular, gym's closure and the need to stay home didn't allow people to perform physical activity easily, with a consequent worsening of cardiovascular risk factors. During quarantine some general recommendations have been disseminated, but little is known about specific guidelines for home–based exercise prescription in patients with cardiovascular disease. Therefore, the purpose of this study is to develop home–based physical exercise programs for cardiac patients referred to the Center for Exercise Science and Sports of University of Ferrara. Methods: On the basis of exercise capacity obtained from the last functional evaluation, performed in presence before the closure, three structured workouts were realized following the guidelines. They are composed as follows: warm–up, strenght and balance exercises alternate to indoor walking, cool–down. Patients received an explicative iconographic via e–mail or smartphone. Some domiciliary sessions were supervised by an operator through video connection. Results: All patients showed excellent compliance with the proposed program. Adherence has been verified through biweekly recalls. No adverse events occurred. Conclusions: Telemonitored exercise prescription in cardiac outpatients was effective and safe, helping to prevent negative consequences of the abrupt cessation of physical activity due to COVID–19 pandemic. These evidence could be useful even after the end of pandemic, for all those patients that are less likely to participate in traditional cardiovascular rehabilitation programs because of difficulties in reaching facilities or leaving home.